INFLUENCE OF HLA-DRB1* ALLELIC SETS ON THE DEVELOPMENT OF TUBERCULOSIS IN CHILDREN - A. A. Starshinova; N. V. Korneva; I. F. Dovgalyuk; M. V. Pavlova; I. E. Pavlova; L. N. Bubnova (Медицинская иммунология, 2015)
According to the WHO data, tuberculosis still represents a serious public health problem worldwide. Deterioration of socio-economic conditions in the population complicates epidemic situation for tuberculosis inRussia, thus leading to increase in acute progressive and complicated forms of tuberculosis in children and, consequently, to worsening structure of its clinical forms. Objectives: to determine associations between certain HLA-DRB1 alleles and risk of tuberculosis development in children. We examined 188 children aged from 3 to 14 years with various manifestations of tuberculous infection. Along with thorough examination of the patients, including multi-spiral CT scans of chest, we undertook genotyping of HLA-DRB1 alleles. Activity of tuberculous infection was determined by a set of immunological tests, i.e., tuberculin skin test, DIASKINTEST® (recombinant allergen of tuberculosis DIASKINTEST®). X ray diagnostics was performed with multi-spiral «Aquilion-32» computed tomograph (Toshiba), according to standard procedures. Molecular genetic typing of HLA-DRB1 alleles was performed by polymerase chain reaction (PCR-SSP), using standard commercial kits PROTRANS Ceclerplate System Protrans HLA-DRB1*. The children were divided into two groups: I group, 90 healthy children, II group, 98 children with tuberculosis. A comparisons group consisted of healthy donors (n = 346). Statistical processing of genetic material included evauation and analysis of the following parameters: frequency distribution of the antigen (F), χ2 criterion for significance (chi-square), the relative risk ratio (RR), etiologic fraction (EF), preventive fraction (PF). Children of the II group had significantly higher *04 allele HLADRB1*, as compared with control group (36.7% vs. 21.1%, χ2 = 10.08; р < 0.01). This finding may suppose a predisposal of these allele carriers to development of tuberculosis. At the same time, the rates of *07 (14.3% vs. 27.5%, χ2 = 7.15, р < 0.01) and *15 (18.4% vs. 28.3%, χ2 = 3.92; р < 0.01) HLA-DRB1* alleles were significantly lower, thus suggesting a protective effect of this allele. *04 allele seems to be a predisposing factor, whereas *07 and *15 alleles are protective for development of tuberculosis in children.